Tendencies of medical education researches in Turkey: Content analysis of 2000-2014 period. - ÖZCAN, Kürşat Volkan; GÖKSU, İdris; KÜÇÜK, Sevda; GÖKTAŞ, Yüksel (Marmara Medical Journal, 2015)
Objectives: The aim of this study is to reveal the tendencies of the researches on medical education in Turkey in terms of instruction levels that the researches took place, methodological dimensions and instructional activities conducted in the researches. Materials and Methods: The sample of the study was composed of researches published in medical journals indexed in ULAKBIM National Database and in PubMed Database between 2000 and 2014. Within this context, the total number of papers was 214. These papers were examined through Medical Education Publication Classification Form (MEPCF) conducting content analysis. Results: As for the results, the participants of most of the studies were the students who were about to graduate. It was observed in the researches that quantitative research method was used most; questionnaires were the most used data collection tool; and instructional activities related to curriculum development and evaluation were used frequently. Conclusion: The results are considered to help the researchers see the trends and tendencies in medical education and assess the field of medical education from different perspectives.